Factors involved in mechanical fatigue degradation of dental resin composites - Lohbauer, Ulrich; Belli, Renan; Ferracane, J. L. (Journal of Dental Research, 2013)
The design of clinical trials allows for limited insights into the fatigue processes occurring in resin composites and the factors involved therein. In vitro studies, in contrast, can fundamentally narrow study interests to focus on particular degradation mechanisms and, to date, represent the major contributors to the state of knowledge on the subject. These studies show that microstructural features are important in determining strength and fracture toughness, whereas fatigue resistance is mainly related to the susceptibility of the matrix and the filler/matrix interface to mechanical and chemical degradation. In this review, we focus on fracture mechanisms occurring during fatigue, on the methods used to assess them, and on additional phenomena involved in the degradation of initial mechanical properties of resin composites. © International & American Associations for Dental Research.
CRIS-Team Scopus Importer:2023-01-23
Keywords: composite resins; crack propagation; cyclic loading; fracture toughness; hydrolysis; viscoelasticity